Effects of different dietary fat sources on growth performances and carcass fatty acid composition of broiler chickens - Azman, MA; Konar, V; Seven, R (Ecole Nationale Veterinaire Toulouse, 2004)
This study was conducted to determine the effects of four different dietary fat sources on performance, fatty acids composition of abdominal fat, thigh skin, breast and thigh muscle of broiler chickens. Soybean oil (SO), poultry grease (PG), beef tallow (BT) and a mixture of soybean oil with poultry grease (SPG 1 : 1) were used as fat source. A total 395, 4-day-old broilers were randomly assigned to 4 groups. The chicks were fed with corn-soy based starter diets containing 4 % of the respective fat source for 21 days, and 6 % of the same fat sources for grower diets for 22-41 days. Final body weight and daily weight gain were higher in broilers fed with SO, and lowest in those fed with SPG. Daily food consumption was significantly higher in SO and BT groups compared to the others (p < 0.05). SO caused marked changes in the fatty acids patterns by significantly decreasing SFA in skin and in abdominal fat and by significantly increasing PUFA (mainly linoleic acid) in skin, in abdominal fat and in breast muscle. On the other hand, BT caused increased accumulation of saturated fatty acids in thigh skins and abdominal fat pad and marked decreases of PUFA in skin, fat and muscles. In the thigh and breast muscle of the PG fed group, oleic acids were significantly increased. In conclusion, feed of broilers with specific mixtures of fatty acids may substantially alter the fat composition of carcass.
Keywords: fat sources; fatty acids; carcass trait; lipid composition; growth; broiler